Past revolutions, future transformations : what can the history of revolutions in military affairs tell us about transforming the U.S. military? - Hundley, Richard O.; Rand Corporation; United States. Defense Advanced Research Projects Agency; National Defense Research Institute (U.S.). Acquisition and Technology Policy Center (Santa Monica, CA : RAND, 1999)
Advances in technology can bring about dramatic changes in military operations, often termed "revolutions in military affairs" or RMAs. Such technology-driven changes in military operations are not merely a recent phenomenon: they have been occurring since the dawn of history, they will continue to occur in the future, and they will continue to bestow a military advantage on the first nation to develop and use them. Accordingly, it is important to the continued vitality and robustness of the U.S. defense posture for the DoD R&D community to be aware of technology developments that could revolutionize military operations in the future, and for the U.S. military services to be on the lookout for revolutionary ways in which to employ those technologies in warfare. This report examines the history of past RMAs, to see what can be learned from them regarding the challenge confronting the DoD today, when it has set out on a concerted effort to bring about a technology-driven transformation of the U.S. military to achieve the operational goals outlined in Joint Vision 2010. Among its many findings are three of particular note: RMAs are rarely brought about by dominant players (such as the U.S. military is today). For a dominant player to bring about an RMA requires a receptive organizational climate, fostering a continually refined vision of how war may change in the future and encouraging vigorous debate regarding the future of the organization; senior officers with traditional credentials willing to sponsor new ways of doing things and able to establish new promotion pathways for junior officers practicing a new way of war; mechanisms for experimentation, to discover, learn, test and demonstrate new ideas; and ways of responding positively to the results of successful experiments, in terms of doctrinal changes, acquisition programs, and force structure modifications. The DoD has some of these elements today, but is missing others. The report makes specific suggestions regarding ways of filling in the missing elements. Doing these things will facilitate DoD's force transformation activities and help ensure that the next RMA is brought about by the United States. and not some other nation.
Introduction --Part 1: Lessons from Past RMAs -- The Characteristics of Revolutions in Military Affairs -- The Breakthough Process Leading to RMAs --Part 2: Being Prepared for Future RMAs (Carried out by Others) -- Being Aware of the Next RMA: the Observables of the Emergence of New RMAs -- Being Responsive to the Next RMA: the Characteristics of a Future-Oriented Military Organization --Part 3: Bringing About Future RMAs (Of Your Own) -- What Does It Take to Bring About a Successful RMA? -- DOD'S Current Force Transformation Activities: Does Anything Appear to Be Missing? What Can Be Done to Fill in the Missing Elements? -- Bibliography.
"National Defense Research Institute."
Includes bibliographical references (p. 91-99).
Also available in Chinese from the publisher (Taipei, Taiwan : Ministry of National Defense).
Also available on the internet via WWW in PDF format.
Keywords: Military art and science -- Technological innovations -- History -- 20th century; Military art and science -- Technological innovations; Military planning -- History -- 20th century; United States -- Armed Forces -- Organization; United States -- Military policy